2013
DOI: 10.1111/aas.12181
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐hospital critical care by anaesthesiologist‐staffed pre‐hospital services in Scandinavia: a prospective population‐based study

Abstract: The incidence of pre-hospital anaesthesiologist patient encounters in Scandinavia varies. Medical aetiology is most frequent. Almost one-quarter of patients presents with deranged vital functions requiring emergency measures. The Scandinavian pre-hospital population incidence of critical illness and injury is 25-30 per 10,000 person-years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
39
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 29 publications
(29 reference statements)
4
39
2
Order By: Relevance
“…In primary emergency helicopter missions, 97.7% of patients were reached within the first hour after dispatch. This result compares well with Krüger et al, who reported 7 min of median activation time and 90% of patients reached within the first hour, but rural HEMS and large SAR helicopters were included in their studies 3, 14. A small helicopter with the crew residing at the HEMS base reduces activation time and thus response time.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In primary emergency helicopter missions, 97.7% of patients were reached within the first hour after dispatch. This result compares well with Krüger et al, who reported 7 min of median activation time and 90% of patients reached within the first hour, but rural HEMS and large SAR helicopters were included in their studies 3, 14. A small helicopter with the crew residing at the HEMS base reduces activation time and thus response time.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the advantage of an experienced anesthesiologist capable of early and sound clinical judgment may be of more value than performing advanced interventions, as the avoidance of an intervention is best practice in some cases. Other researchers have found that advanced treatment was performed in only 23.1% of HEMS missions, but they included several rural services and used a different study design 14. The use of HEMS has changed slightly in recent years, with a focus on rapid transport to a hospital with appropriate medical, high‐tech interventions in patients suffering myocardial infarction or stroke.…”
Section: Discussionmentioning
confidence: 99%
“…It was also associated with more and faster transports directly to a trauma centre compared to dispatch by a paramedic at the dispatch centre 25. A Scandinavian study on anaesthesiologist‐staffed pre‐hospital services found a population incidence of critical illness or injury of 11 per 10,000 person‐years in Norway, based on deranged vital signs, advanced medical procedures performed, and advanced medication given 2. The proportion of trauma patients in the study was 39%, and 27% were considered to have severely deranged vital signs 2…”
Section: Discussionmentioning
confidence: 99%
“…Systems differ between countries, as does the use of physicians vs. paramedics. Both offer extended skills and treatment modalities as compared to ordinary ground ambulances 2. The advanced pre‐hospital care may be delivered through Helicopter Emergency Medical Services systems or rapid response/emergency cars (collectively designated as HEMS).…”
mentioning
confidence: 99%
See 1 more Smart Citation